Wage persistence and labour market institutions: an analysis of young European workers - Antonio Menezes; Dario Sciulli; José António Cabral Vieira (Institute for the Study of Labor (IZA), 2007)
This paper investigates the effects of labour market institutions on wage persistence among young European workers at the beginning of their careers. We use ECHP data from 1995 to 2001 for 13 EU countries and estimate a three-level random intercept probit model that allows for unobserved heterogeneity both at the individual and country level. Overall, we find that labour market institutions explain wage persistence. In particular, we find that a high level of employment protection legislation and a high level of bargaining centralization increase wage persistence
urn:nbn:de:101:1-20080416370
Keywords: 330; Lohnrigidität; Jugendliche Arbeitskräfte; Arbeitsmarktflexibilisierung; Kündigungsschutz; Tarifpolitik; EU-Staaten